2020
DOI: 10.1016/j.rmed.2019.105820
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decline in quality of life in smokers without airflow obstruction: The COPDGene study

Abstract: Current and former smokers with normal spirometry and with Preserved Ratio Impaired Spirometry (PRISm) experience respiratory events similar to chronic obstructive pulmonary disease (COPD) exacerbations. Exacerbations significantly reduce quality of life (QoL) in COPD patients however the effect of respiratory exacerbations on QoL in these groups is unknown. We hypothesized that exacerbations and change in exacerbation status would predict QoL decline among normal spirometry and PRISm participants in COPDGene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“… 20 , 34 In the current study, we found that current smokers had the highest prevalence of airflow limitation and PRISm, and it is known that continued smoking and the onset of frequent exacerbations are predictors of declining quality of life in smokers with PRISm. 35 These findings support the screening of individuals 40 years of age or older who are current or former smokers to facilitate early diagnosis of COPD and identify those at risk of developing COPD or at increased risk of COPD-related mortality. 36 Specifically, such individuals should undergo spirometry testing for COPD diagnosis and should be offered smoking cessation, dietary, and exercise interventions.…”
Section: Discussionsupporting
confidence: 66%
“… 20 , 34 In the current study, we found that current smokers had the highest prevalence of airflow limitation and PRISm, and it is known that continued smoking and the onset of frequent exacerbations are predictors of declining quality of life in smokers with PRISm. 35 These findings support the screening of individuals 40 years of age or older who are current or former smokers to facilitate early diagnosis of COPD and identify those at risk of developing COPD or at increased risk of COPD-related mortality. 36 Specifically, such individuals should undergo spirometry testing for COPD diagnosis and should be offered smoking cessation, dietary, and exercise interventions.…”
Section: Discussionsupporting
confidence: 66%
“…These are all indicators of the main factors that may affect the perception of QoL for these patients in Jordan, probably internationally as well. 5,11,14,15,18,33,39 Therefore, these constitute reasonable goals for the healthcare service providers and planners to target to improve the QoL perceptions among patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…8 The correlation between COPD symptom load and anxiety and depression is important, as the combination of these disorders can worsen the disease course, duration, and outcome. 9 Studies have shown that COPD negatively correlates with the Quality of Life (QoL), [10][11][12][13][14][15][16][17] and this correlation worsens as the severity increases. Kushwaha et al (2020) reported "impaired" life processes and health-related quality of life among patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors include age, female sex, a history of smoking, diabetes mellitus, and obesity 5,7,15,16 . Moreover, increased dyspnoea, reduced 6-min walk distance 1 , and reduced health-related quality of life 17,18 have been reported in individuals with PRISm.The Genetic Epidemiology of COPD (COPDGene) study and other reports discussing PRISm 1-3,8,18 have explained the condition using medical data 4,6,9 . However, few studies have focused on community-dwelling individuals 7 .…”
mentioning
confidence: 99%
“…Risk factors include age, female sex, a history of smoking, diabetes mellitus, and obesity 5,7,15,16 . Moreover, increased dyspnoea, reduced 6-min walk distance 1 , and reduced health-related quality of life 17,18 have been reported in individuals with PRISm.…”
mentioning
confidence: 99%